2018
DOI: 10.1530/jme-17-0311
|View full text |Cite
|
Sign up to set email alerts
|

40 YEARS OF IGF1: IGF1 receptor signaling pathways

Abstract: Insulin-like growth factors (IGFs) bind specifically to the IGF1 receptor on the cell surface of targeted tissues. Ligand binding to the α subunit of the receptor leads to a conformational change in the β subunit, resulting in the activation of receptor tyrosine kinase activity. Activated receptor phosphorylates several substrates, including insulin receptor substrates (IRSs) and Src homology collagen (SHC). Phosphotyrosine residues in these substrates are recognized by certain Src homology 2 (SH2) domain-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
238
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(287 citation statements)
references
References 149 publications
5
238
0
2
Order By: Relevance
“…The IGF-IR gene is mapped to chromosome 15q25-26. Activation of receptor tyrosine kinase activity results from ligand binding to the α subunit of the receptor leading to a conformational change in the β subunit (160). This leads to the activation of downstream signaling pathways of IGFs including PI 3-kinase pathway and Ras-mitogen-activated protein kinase (MAP kinase) pathway, for cell proliferation, cell differentiation and cell survival (160).…”
Section: Igf-i Receptor and Intracellular Signalingmentioning
confidence: 99%
“…The IGF-IR gene is mapped to chromosome 15q25-26. Activation of receptor tyrosine kinase activity results from ligand binding to the α subunit of the receptor leading to a conformational change in the β subunit (160). This leads to the activation of downstream signaling pathways of IGFs including PI 3-kinase pathway and Ras-mitogen-activated protein kinase (MAP kinase) pathway, for cell proliferation, cell differentiation and cell survival (160).…”
Section: Igf-i Receptor and Intracellular Signalingmentioning
confidence: 99%
“…The explanation for the increase in efficacy may be the massive production of IGF1 by ASC.B6 cells, which contributes to the 4T1 cell proliferation in an in vitro assay (13). We show here that ASC.B6derived factors induce Akt phosphorylation, hence switch on the PI3K/Akt signaling pathway, and thereby promote cell survival, proliferation, growth and cellular metabolic pathways (17,21) In addition, we have identified IGFBP2 in the secretome of vASCs, which sequesters IGF1 and thereby regulates its accessibility and function (15). IGFBP2 was missing from ASC.B6 cells, and supplementation with a recombinant protein abolished tumor cell proliferation, and also mitigated the ASC.B6-induced Akt phosphorylation.…”
Section: Discussionmentioning
confidence: 70%
“…IGF1 is a general mitogen, it induces pro-survival signaling pathways, such as the Ras/MAPK and the PI3K/Akt kinase pathway (17). When we added ASC.B6 conditioned medium to 4T1 cells, it rapidly induced Akt phosphorylation, with a maximum at 5 min (Figure 3A).…”
Section: Igf1/igfbp2 Balance the Survival Signaling Pathway Of Breastmentioning
confidence: 98%
“…IGF-1 bound activated IGF-1R phosphorylates insulin receptor substrates (such as IRS1, IRS2 and Shc). The Src homology 2 (SH2) domains of these substrates are recognized by signaling molecules to activate the intracellular effectors such as RAS, RAF and SOS and the RAS/MAPK pathway [36,37]. Interestingly, in our previous study, we observed significant downregulation of NRAS with miR-29a overexpression in PDAC cell lines [38].…”
Section: Igf-1 Belonging To the Igf Family Members Is One Of The Kementioning
confidence: 81%
“…Network analysis with the targets identified three overlapping pathways related to IGF, RAS/MAPK signaling and laminin interactions. IGF-1 secreted by activated PSCs and CAFs via sonic hedgehog pathway activates IGF-1R in cancer cells triggering phosphorylation of insulin-receptor or Src substrates to promote PDAC metastasis via intracellular pathways such as RAS/MAPK [36,52]. In addition, high IGF-1 with low IGFBP3 expressions associated with enhanced risks for PDAC [53].…”
Section: Discussionmentioning
confidence: 99%